Occurrences of mineral resources in Bandipur Gondrang area of Tanahun district, central Nepal, Lesser Himalaya - Paudyal, Kabiraj (Journal of Science and Engineering, 2014)
A detailed geological investigation was carried out to assess the distribution of minerals and their geological control in Bandipur-Gondrang area of Tanahu district, a part of Lesser Himalaya in central Nepal. The area is found rich in both metallic and non-metallic mineral deposits. The main metallic minerals found are iron in Phalamdada and Labdi Khola, copper in Bhut Khola and poly-metallic deposits including suspected gold in Bhangeri Khola and Jaubari Khola-Bar Khola sections. A large deposit of inorganic carbon is found around the Gondrang-Watak area. Similarly, a good quality of green marble (metabasite) is found as decorative stone in Bagar Khola area and good quality of roofing stone in Bandipur area. In addition to these economic deposits other several sub economic to non-economic mineral are also located in the geological map of the area. Categorization of these mineral deposits is based on the probable reserve and laboratory analysis of related samples. Geological control of mineral deposits is considered to be the stratigraphic, structural, metamorphic and hydrothermal. Iron mineralization of the area is found stratigraphical control, copper deposits by magmatism of basic rocks (amphibolites), and poly-metallic deposits are related to the hydrothermal processes.